Do migrants and locals differ in commuting behavior? A case study of Xiamen, China. (July 2021) - Li, Yongling; Geertman, Stan; Hooimeijer, Pieter; Lin, Yanliu; Yang, Haoran
Abstract: Although there is a growing body of literature on the commuting pattern of rural migrants in China, few studies have examined the diversity in commuting behavior among workers with different occupations. The present research used the 2015 Xiamen household travel survey to examine commuting distances and commuting times of distinctive types of workers in the city. The results reveal differences in commuting behaviors among distinctive socioeconomic groups, namely blue-collar, pink-collar, or white-collar local or migrant workers. For local residents, blue-collar workers have the longest commute distance, while pink-collar workers have the shortest commute distance. Migrant workers—for both blue-collar and pink-collar—in general commute over shorter distances than local workers to reach their workplaces. However, planning practices have attempted to demolish their affordable rental housing in urban villages, which will increase their commuting times and costs and exacerbate sociospatial inequality. These findings can be of practical use when offering alternative housing for migrants in urban redevelopment.